2012
DOI: 10.1016/j.pmrj.2011.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The Reproducibility of Berg Balance Scale and the Single‐Leg Stance in Chronic Stroke and the Relationship Between the Two Tests

Abstract: The BBS and the SLS are reproducible measurements in patients with chronic stroke, but only the BBS is sensitive enough to follow changes over time or after an intervention. The SLS is strongly related to the BBS and can be used as an independent test to measure upright postural control after a stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(78 citation statements)
references
References 25 publications
4
71
1
1
Order By: Relevance
“…We found all three BESTest measures to correlate moderately with the TUG (r = À0.60 to À0.68) which falls within the range of correlations previously demonstrated between other performance-based balance tests and the TUG in older adults (r = À0.69 to À0.83) [23]. We also found moderate to high correlations between the BESTest measures and the SLS (r = 0.67-0.77), consistent with previous work showing a similar associations between the SLS and another multi-item dynamic balance test in older adults with chronic stroke (r = 0.65-0.79) [24]. The full BESTest and brief-BESTest have not previously been studied in relation to the TUG or SLS, but the mini-BESTest has been shown to be associated with both in individuals with chronic stroke [25].…”
Section: Discussionsupporting
confidence: 90%
“…We found all three BESTest measures to correlate moderately with the TUG (r = À0.60 to À0.68) which falls within the range of correlations previously demonstrated between other performance-based balance tests and the TUG in older adults (r = À0.69 to À0.83) [23]. We also found moderate to high correlations between the BESTest measures and the SLS (r = 0.67-0.77), consistent with previous work showing a similar associations between the SLS and another multi-item dynamic balance test in older adults with chronic stroke (r = 0.65-0.79) [24]. The full BESTest and brief-BESTest have not previously been studied in relation to the TUG or SLS, but the mini-BESTest has been shown to be associated with both in individuals with chronic stroke [25].…”
Section: Discussionsupporting
confidence: 90%
“…This was 1.71 (out of 56) higher than the control group's score of 1.36. The MDC of BBS was known to be lying between 2.5 and 4.13 (Liston and Brouwer, 1996;Flansbjer et al, 2012). The highest score of BBS in this study was 43 score (out of 6, 9.8%) in this study.…”
Section: ⅳ Discussionsupporting
confidence: 43%
“…In previous studies, Flansbjer and colleagues 58,59 reported 95% CIs of the smallest real difference as -0.15 to 0.25m/s for comfortable walking speed, -3.4 to 4.9 points for the Berg Balance Scale and -3.8 to 2.6 seconds for the Timed Up and Go Test for individuals with chronic hemiparesis subsequent to stroke. Even though the smallest real difference is not an instrument to define clinical relevance, the fact that the noted effects were smaller than the smallest real difference limits the ability to conclude that these were real improvements.…”
Section: Discussionmentioning
confidence: 94%